ICT Integration and In-service Training: A Catalyst for Improved Job Performance among Non-Teaching Staff in Nigerian Tertiary Institutions - Adegoke, Sunmola Kadiri; Akanbi, Adekemi Olufunke (African Journal of Behavioural and Scale Development Research, 2025)
Abstract The study investigated the effect of an in-service training with information and communication technology components on job performance among non-teaching staff in tertiary institutions in Osun state, Nigeria. This was with the aim of establishing a synergy between in-service training and performance on job of non-academic staff of the institutions. Thirty (30) non-academic staff were randomly selected from each of three institutions purposefully selected from the four existing tertiary institutions owned by the state. This yielded a sample size of ninety (90) for the study. The three selected institutions were by purposeful selection designated Experimental group1(whose training was reinforced with monitoring), Experimental group 2 (who were exposed to training without monitoring) and the Control group, who were not administered any form of intervention. An instrument of data collection was a Job Performance Evaluation Format (JPEF) administered by the immediate supervisors of the sampled staff to measure their job performance before and at the end of training. Data was collected and analyzed using Analysis of Variance (ANOVA). The results of the analysis revealed a significant difference in job performance of the experimental groups and control group at the of the training (F(2,87) = 14.44, p < 0.05). The results particularly, showed that in-service training that was reinforced with monitoring significantly enhanced job performance of the non-academic staff in the institutions better than that without monitoring (Scheffe, mean difference 5.90, p < 0.05) and significantly better than the control group (Scheffe, mean difference 9.70, p < 0.05). The training without monitoring did not significantly enhanced the job performance of the staff (Scheffe, mean difference 3.80, p > 0.05). The study concluded that in-service training that is reinforced with monitoring significantly enhanced the performance on the job of the non-teaching staff of the institutions.